Implementasi Kebijakan Anti Bullying dalam Mewujudkan Sekolah Ramah Anak di Kota Gorontalo - Dwi Rahmadania Salmon, Sri; Rusdiyanto U Puluhulawa, Mohamad; Taufiq Zulfikar Sarson, Mohamad (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
Bullying or harassment in educational environments is a form of violence that threatens children's basic rights to live, grow, and develop safely as guaranteed by Article 28B paragraph (2) of the 1945 Constitution. This phenomenon not only shows weak institutional supervision, but also reflects the failure of legal and social culture in protecting students from physical, verbal, and psychological violence. The purpose of this study is to increase public awareness about the importance of creating a child-friendly and bullying-free school environment and to reduce the incidence of bullying in schools in Gorontalo City. This study uses an empirical legal approach supported by a normative approach, by examining bullying practices at State Senior High School 7, Gorontalo City through field observations, interviews, and documentation. The results of the study show that bullying occurs systematically and repeatedly, driven by psychological factors of the perpetrators, the social environment of peers, weak enforcement of school rules, and a culture of seniority. Bullying has a serious impact on the mental development of victims, such as decreased self-confidence, anxiety, and even the desire to end their lives. Efforts to overcome this are carried out through penal and non-penal strategies, including the implementation of the Child Protection Law and Permendikbudristek No. 46 of 2023. The conclusion of this study emphasizes the importance of collaboration between schools, parents, BK teachers, and law enforcement in creating a safe and inclusive learning space. Recommendations include strengthening supervision, counseling, character education, and the application of academic sanctions against perpetrators of bullying to create a deterrent effect. With a holistic approach, bullying can be prevented as a real step towards fulfilling children's rights and transforming a civilized education culture.